Analytical survey of the predator-prey model with fractional derivative order - Abbagari, Souleymanou; Houwe, Alphonse; Saliou, Youssoufa; Douvagai; Chu, Yu-Ming; İnç, Mustafa; Doka, Serge Y. (Aip Publishing, 2021)
This work addresses the analytical investigation of the prey-predator behavior modeled by nonlinear evolution equation systems with fractional derivative order. Through the New Extended Algebraic Method (NEAM), we unearthed diverse types of soliton solutions including bright, dark solitons, combined trigonometric function solutions, and singular solutions. Besides the results obtained in the work of Khater, some new complex soliton solutions are also unearthed. The NEAM can also be used like the synthesis of the two mathematical tools.
Keywords: Nonlinear Schrodinger-Equation; Traveling-Wave Solutions; Optical Solitons; Propagation; Dispersion; Evolution